Aplikasi multimedia dalam penyebaran maklumat di TV3 / Zuraida Mohd Aziz - Zuraida, Mohd Aziz (2004)
Information is an essential element in life. There are variety of methods that can be used to acquire information. Information can be obtained or via printed of electronics media such as television, internet, magazine, newspapers and many others. Observing, content analysis, primary source studies and interview are methods that have be used to carry out this research. Nowadays, to own television for single house is not burden anymore. Television is a popular social equipment that plays the roll of information dissemination medium. This is because television is a record of important events and a symbol of civilization technology department. To simplify the process of disseminations information, TV3 uses variety of multimedia elements to ensure this process going smoother, faster and easily captured by public. The multimedia element that have been used are texts, audios, visuals/images/pictures, videos and graphics. How ever, there is another element that has being used widely that is animation. This element is used more in commercial advertisement, animation and fiction science film production.